(untitled) (Journal of the College of Basic Education, 2025)
The Disagreement over translating Phonetics terms into Arabic is apparent in the modern Arabic Phonetics lesson. Our research was limited to the Disagreement surrounding the translation of the verbal term in linguistic dictionaries composed by Arab linguists. We have chosen a number of these Phonetics terms to be a sample that reveals this Disagreement and its impact on the study of modern Arabic Phonetics. They were 10 terms, 6 of the Phonetics terms Phonetics: Consonant، Vowel، Occlusive، Spirant، Glides، Liquid. And 4 phonology terms Phonology: Phonology، Phoneme، Allophone، وSuprasegmental. Our study included 12 dictionaries from 1982 to 2012.